A kind of high hardness alumina-based ceramic and preparation method thereof
Through specific formulas and high-temperature sintering processes, the hardness and fracture toughness of alumina-based ceramics are improved, and the problem of insufficient hardness and toughness of traditional alumina-based ceramics is solved, and the preparation of high hardness and high density ceramic materials is achieved.
Patent Information
- Application Number
- CN202410437642.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-04-12
AI Technical Summary
Alumina-based ceramics are difficult to improve fracture toughness while increasing hardness. The introduction of traditional toughening agents will increase the sintering temperature and thermal stress, affecting the overall performance of the material.
88 to 90 parts of alumina, 5 to 7 parts of zirconia, 2 to 4 parts of lanthanum bored modified barium titanate, 1 to 3 parts of zirconia modified silicon carbide, 6 to 8 parts of sintering aid, 1 to 2 The formula of parts of polyacrylic acid, 1 to 2 parts of sodium alginate, 0.5 to 1.0 parts of triammonium citrate and 15 to 20 parts of solvent is formed by spray granulation and high-temperature sintering.
It effectively improves the density, hardness and fracture toughness of alumina-based ceramics, reduces thermal stress, and enhances the mechanical properties and high temperature stability of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic manufacturing, in particular to a high-hardness alumina-based ceramic and a preparation method thereof. Background Art
[0002] Alumina-based ceramics are an industrial material with physical and chemical properties such as high hardness and high corrosion resistance. They are widely used in cutting tools, machinery manufacturing, electronic devices, aerospace and other fields. At present, zirconium oxide is usually used in alumina-based ceramics to improve strength, but a high content of zirconium oxide will hinder the elongation and deformation of the alumina ceramic matrix, causing its mechanical strength to decrease. On the other hand, the biggest disadvantage of alumina-based ceramics is the low fracture toughness. Toughening agents such as magnesium oxide are often used, but their introduction will increase the sintering temperature. Due to the different physical properties of the substances in the raw materials, there are thermal stresses at the contact interface, which leads to cracks in the material, affecting the toughness and mechanical strength of the overall material.
[0003] In summary, it is of great significance to prepare a high-hardness alumina-based ceramic, solve the technical difficulties in traditional alumina-based ceramics, and improve the mechanical properties of ceramic materials such as fracture toughness while ensuring high hardness, so as to meet the needs of different application fields and provide new possibilities for application expansion. Summary of the invention
[0004] The object of the present invention is to provide a high-hardness alumina-based ceramic and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A high-hardness alumina-based ceramic comprises the following raw materials in parts by mass: 88 to 90 parts of alumina, 5 to 7 parts of zirconium oxide, 2 to 4 parts of lanthanum boride-modified barium titanate, 1 to 3 parts of zirconium oxide-modified silicon carbide, 6 to 8 parts of sintering aids, 1 to 2 parts of polyacrylic acid, 1 to 2 parts of sodium alginate, 0.5 to 1.0 parts of triammonium citrate, and 15 to 20 parts of solvent.
[0007] In a further embodiment, the method for preparing the lanthanum boride modified barium titanate comprises the following steps:
[0008] Step 1: add barium hydroxide to deionized water and heat to dissolve; add nano-titanium dioxide and ethanol dispersion at room temperature and stir evenly; use ammonia water to adjust the pH to 12.6-13.2 to obtain a mixed solution; perform a hydrothermal reaction on the mixed solution at 250-270° C. for 20-50 hours, cool, wash and dry to obtain barium titanate;
[0009] Step 2: Mix the lanthanum compound, sodium metaborate, barium titanate and triammonium citrate and ball-mill to obtain a mixed powder, which is heat-treated at 200-300° C. for 2 hours; after cooling, the mixed powder is washed with hydrochloric acid and deionized water, dried, and ground to obtain lanthanum boride-modified barium carbonate.
[0010] In a further embodiment, the lanthanum boride-modified barium carbonate includes the following raw materials in parts by weight: 2 to 5 parts of lanthanum compound, 4 to 8 parts of sodium metaborate, 2 to 4 parts of barium titanate, and 0.2 to 0.5 parts of triammonium citrate.
[0011] In a further embodiment, the lanthanum compound includes but is not limited to one or more of lanthanum nitrate, lanthanum oxalate, lanthanum carbonate, and lanthanum hydroxide.
[0012] In a further embodiment, the sintering aid comprises a composition of magnesium oxide, nano titanium dioxide, glass powder and niobium pentoxide in a mass ratio of 1:(1-1.2):(1.2-1.5):(0.3-0.6).
[0013] In a further embodiment, the raw materials in the barium titanate include barium hydroxide and nano-titanium dioxide in a mass ratio of (9.5-10):1.
[0014] In a further embodiment, the method for preparing zirconium oxide modified silicon carbide comprises the following steps:
[0015] Step 1: placing silicon carbide in an acidic solution, stirring at 25-35° C. for 1-2 hours, adjusting to neutrality, filtering, washing, and drying to obtain pretreated silicon carbide;
[0016] Step 2: placing the pretreated silicon carbide in yttrium-stabilized zirconium oxide sol, adding deionized water, polyacrylic acid, polyethylene glycol, and polyvinyl alcohol; ball milling and mixing, filtering and drying, and obtaining zirconium oxide-modified silicon carbide.
[0017] In a further embodiment, the acidic solution is a 5-6wt% hydrochloric acid solution; the zirconium oxide modified silicon carbide includes the following raw materials in parts by weight: 6-8 parts of pretreated silicon carbide, 2-3 parts of yttrium stabilized zirconium oxide sol, 0.05-0.1 parts of polyacrylic acid, 0.05-0.1 parts of polyethylene glycol, 0.05-0.1 parts of polyvinyl alcohol, and 10-12 parts of deionized water.
[0018] In a further embodiment, a method for preparing a high-hardness alumina-based ceramic comprises the following steps:
[0019] Step 1: Add zirconium oxide modified silicon carbide, polyacrylic acid, sodium alginate and a sintering aid into deionized water in sequence, homogenize by ball milling, filter and dry to obtain raw material A;
[0020] Step 2: Add raw material A, aluminum oxide, zirconium oxide, lanthanum boride-modified barium titanate, and triammonium citrate into a solvent in sequence, perform ball milling homogenization, and perform spray granulation to obtain granulated powder;
[0021] Step 3: Press the granulated powder into a blank, sinter it, grind and polish the surface to obtain a high-hardness alumina-based ceramic.
[0022] In a further scheme, in step 2, the parameters of spray granulation are: the inlet temperature is 250-300°C, the flow rate is 2-5kg / h, and the outlet temperature is 90-100°C; in step 3, the parameters of the pressed blank are: dry pressing pre-pressing at 15-20MPa, and static pressing final pressing at 200-230Mpa; the parameters of the sintering process are: under a vacuum degree of <0.1MPa, heating to 700-800°C at a rate of 4-5°C / min, and keeping warm for 1-2 hours; heating to 1300-1400°C at a rate of 5-10°C / min, and keeping warm for 2-3 hours; heating to 1500-1700°C at a heating rate of 5-10°C and keeping warm for 2-3 hours; cooling to 1300-1400°C, keeping warm for 10-15min at 80Mpa, sintering is completed, and the temperature is naturally cooled.
[0023] The beneficial effects are as follows: In the scheme, alumina is used as the main body, zirconium oxide is added as a toughening agent, lanthanum boride-modified barium titanate and zirconium oxide-modified silicon carbide are used as toughening agents, and sintering aids are introduced to improve sintering performance, effectively improving the density of alumina-based ceramics and increasing mechanical properties such as hardness and fracture toughness.
[0024] In scheme (1), lanthanum boride-modified barium titanate is introduced, which is a composite material of barium titanate and lanthanum boride. Its introduction can effectively improve the hardness, fracture toughness and strength of alumina-based ceramics.
[0025] Among them, the introduction of barium titanate can, firstly, improve the processing performance; secondly, it can effectively improve the thermal expansion properties of alumina-based ceramics, thereby reducing thermal stress and improving fracture toughness; thirdly, it can promote the sintering between inorganic particles, thereby effectively enhancing the density of ceramic materials and increasing strength.
[0026] Among them, the scheme further compounds lanthanum boride. Under the high temperature of the sintering process, firstly, lanthanum hexaboride with high hardness can be formed, and borates can be produced to form a solid solution with alumina, thereby increasing the density. Second, it can form fine lanthanum diboride particles with alumina at the grain boundaries, thereby hindering the slip and expansion of the grain boundaries and improving the toughness and hardness of the material. Lanthanum boride can also enhance the high-temperature stability of alumina-based ceramics. Third, the lanthanum element it contains is a rare earth element, and the ion radius and the interface energy of alumina are relatively low, which is conducive to stability. It can cooperate with the yttrium element contained in zirconium oxide-modified silicon carbide to reduce the strain difference between lattices, reduce stress accumulation, and enhance performance.
[0027] In addition, the combination of barium titanate and lanthanum boride will generate compounds with higher melting points during high-temperature processes, and a perovskite phase will be produced, thereby enhancing the hardness and high-temperature stability of the ceramic.
[0028] (2) In the scheme, zirconium oxide modified silicon carbide was introduced. Silicon carbide is a high-strength, high-modulus, high-temperature resistant reinforcement. It has dispersion problems in alumina-based ceramics. Therefore, in the scheme, zirconium oxide sol is loaded on its surface to enhance the dispersion and further enhance the fracture toughness of alumina-based ceramics.
[0029] In the specific scheme, zirconium oxide modified silicon carbide is a zirconium oxide modified silicon carbide obtained by loading zirconium oxide sol on the surface based on silicon carbide, and it is pre-compounded with a sintering aid under the action of polyacrylic acid and sodium alginate to obtain raw material A. Since raw material A contains sodium alginate, it will promote gelation. Therefore, during the high-temperature sintering process, the size of the zirconium oxide grains on the surface of silicon carbide is relatively small, resulting in a nano effect, which increases the strength of alumina-based ceramics. At the same time, under the action of sodium alginate and with the aid of niobium pentoxide, the anisotropy of the surface zirconium oxide grains is increased, and irregularly shaped zirconium oxide is produced, which increases the density while reducing the initial stress, producing a toughening mechanism similar to whisker extension, thereby effectively toughening and strengthening the alumina-based ceramics.
[0030] In the scheme (3), the sintering aid includes a composition of magnesium oxide, nano-titanium dioxide, glass powder, and niobium pentoxide. Compared with the common sintering aids, this formula has better sintering performance.
[0031] Among them, magnesium oxide and titanium dioxide can form composite oxides, improve the grain boundary diffusion rate and the activity of inorganic materials, thereby promoting the sintering process; glass powder, magnesium oxide and titanium dioxide can be eutectic at high temperature to form a liquid phase, prevent particle agglomeration while filling the gaps in inorganic materials to improve density; and niobium pentoxide can promote the thermal decomposition of organic components such as polyacrylic acid and sodium alginate in the material, promote the sintering process, and form a liquid phase with alumina and other sintering aids, further improving the density and mechanical properties of alumina-based ceramics. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that the following specific embodiments are parts by mass; at the same time, the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: the CAS number of triammonium citrate is 3458-72-8, the CAS number of sodium metaborate is 7775-19-1, the CAS number of polyvinyl alcohol is 9002-89-5, the CAS number of polyacrylic acid is 9007-16-3, the CAS number of sodium alginate is 9005-38-3, and the polyethylene glycol is polyethylene glycol 400, all of which are commercially available; the CAS number of barium hydroxide is 17194-00-2, which is provided by Sichuan South China Inorganic Salt Co., Ltd.; the purity of lanthanum carbonate is ≥99.5 %, provided by Shanghai Fuzhe Chemical Co., Ltd.; the average particle size of nano titanium dioxide is 20nm, and the average particle size of niobium pentoxide is 100nm, both provided by Yamei Nano Technology Co., Ltd.; the length of silicon carbide is 50-100μm, provided by Shanghai Jingkang Bioengineering Co., Ltd.; aluminum oxide is α-aluminum oxide, provided by Shanghai Baishun Biotechnology Co., Ltd.; the purity of zirconium oxide is 99.5%, provided by Henan Yejiusheng Industrial Co., Ltd.; the purity of magnesium oxide is 99.9%, provided by Wuhan Haishan Technology Co., Ltd.; the glass powder contains the following components: 20-26wt% of calcium oxide, 12-18wt% of aluminum oxide, and the rest is silicon dioxide;
[0034] The preparation method of yttrium-stabilized zirconia sol is as follows: yttrium chloride and zirconium oxychloride with a molar ratio of 3:100 are sequentially added into a 75wt% ethanol aqueous solution, wherein the total mass of yttrium chloride and zirconium oxychloride accounts for 35wt% of the ethanol aqueous solution; hydrogen peroxide is added, the molar ratio of hydrogen peroxide to zirconium oxychloride is 1:5, the mixture is stirred evenly, 1mol / L ammonia water is added dropwise, the pH is adjusted to 8.6, the mixture is stirred evenly, and yttrium-stabilized zirconia sol is obtained.
[0035] Embodiment 1: A method for preparing a high-hardness alumina-based ceramic, comprising the following steps:
[0036] Step 1: Preparation of lanthanum boride modified barium titanate: (1) Add 10 parts of barium hydroxide to 15 parts of deionized water, heat to 80°C and stir to dissolve; at room temperature, add 1 part of a dispersion of nano titanium dioxide and 15 parts of ethanol and stir evenly; use ammonia water to adjust the pH to 13.1 to obtain a mixed solution; subject the mixed solution to a hydrothermal reaction at 260°C for 30 hours, cool, wash and dry to obtain barium titanate; (2) Mix 5 parts of lanthanum carbonate, 7.5 parts of sodium metaborate, 4 parts of barium titanate and 0.3 parts of triammonium citrate and ball mill to obtain a mixed powder, which is heat treated at 250°C for 2 hours; after cooling, wash with 5wt% hydrochloric acid and deionized water, dry and grind to obtain lanthanum boride modified barium carbonate;
[0037] Preparation of zirconium oxide modified silicon carbide: (1) placing silicon carbide in a 5wt% acidic solution, stirring at 30°C for 2 hours, adjusting to neutrality, filtering, washing and drying to obtain pretreated silicon carbide; (2) placing 7 parts of pretreated silicon carbide in 3 parts of yttrium stabilized zirconium oxide sol, adding 10 parts of deionized water, 0.05 parts of polyacrylic acid, 0.05 parts of polyethylene glycol and 0.05 parts of polyvinyl alcohol; ball milling, filtering and drying to obtain zirconium oxide modified silicon carbide;
[0038] Step 2: (1) Mix magnesium oxide, nano titanium dioxide, glass powder and niobium pentoxide in a mass ratio of 1:1:1.4:0.6 to obtain a sintering aid; (2) Add 2 parts of zirconium oxide modified silicon carbide, 1 part of polyacrylic acid, 1.5 parts of sodium alginate and 8 parts of the sintering aid into deionized water in sequence, ball mill homogenize, filter and dry to obtain raw material A;
[0039] Step 3: Add raw material A, 89 parts of aluminum oxide, 6 parts of zirconium oxide, 3 parts of lanthanum boride-modified barium titanate, and 0.5 parts of triammonium citrate to 20 parts of ethanol in sequence, ball mill homogenize, set the inlet temperature to 300° C., the flow rate to 4.5 kg / h, and the outlet temperature to 100° C., and perform spray granulation to obtain granulated powder;
[0040] Step 4: Pre-press the granulated powder by dry pressing at 20MPa, and final press it by static pressing at 200Mpa to form a blank; place it in a high-temperature furnace, and heat it to 800℃ at a rate of 5℃ / min under a vacuum degree of <0.1MPa, and keep it warm for 1 hour; heat it to 1350℃ at a rate of 8℃ / min, and keep it warm for 2 hours; heat it to 1600℃ at a heating rate of 8℃ and keep it warm for 3 hours; cool it to 1350℃, keep it warm at 80Mpa for 10min, finish sintering, and cool it naturally; grind and polish the surface to obtain high-hardness alumina-based ceramics.
[0041] Embodiment 2: A method for preparing a high-hardness alumina-based ceramic, comprising the following steps:
[0042] Step 1: Preparation of lanthanum boride modified barium titanate: (1) Add 10 parts of barium hydroxide to 15 parts of deionized water, heat to 80°C and stir to dissolve; at room temperature, add 1 part of a dispersion of nano titanium dioxide and 15 parts of ethanol and stir evenly; use ammonia water to adjust the pH to 13.1 to obtain a mixed solution; subject the mixed solution to a hydrothermal reaction at 260°C for 30 hours, cool, wash and dry to obtain barium titanate; (2) Mix 5 parts of lanthanum carbonate, 7.5 parts of sodium metaborate, 4 parts of barium titanate and 0.3 parts of triammonium citrate and ball mill to obtain a mixed powder, which is heat treated at 250°C for 2 hours; after cooling, wash with 5wt% hydrochloric acid and deionized water, dry and grind to obtain lanthanum boride modified barium carbonate;
[0043] Preparation of zirconium oxide modified silicon carbide: (1) placing silicon carbide in a 5wt% acidic solution, stirring at 30°C for 2 hours, adjusting to neutrality, filtering, washing and drying to obtain pretreated silicon carbide; (2) placing 7 parts of pretreated silicon carbide in 3 parts of yttrium stabilized zirconium oxide sol, adding 10 parts of deionized water, 0.05 parts of polyacrylic acid, 0.05 parts of polyethylene glycol and 0.05 parts of polyvinyl alcohol; ball milling, filtering and drying to obtain zirconium oxide modified silicon carbide;
[0044] Step 2: (1) Mix magnesium oxide, nano titanium dioxide, glass powder and niobium pentoxide in a mass ratio of 1:1:1.5:0.5 to obtain a sintering aid; (2) Add 1 part of zirconium oxide modified silicon carbide, 2 parts of polyacrylic acid, 1 part of sodium alginate and 6 parts of sintering aid to deionized water in sequence, ball mill homogenize, filter and dry to obtain raw material A;
[0045] Step 3: Add raw material A, 90 parts of aluminum oxide, 5 parts of zirconium oxide, 4 parts of lanthanum boride-modified barium titanate, and 0.5 parts of triammonium citrate to 15 parts of ethanol in sequence, ball mill homogenize, set the inlet temperature to 300°C, the flow rate to 4.5 kg / h, and the outlet temperature to 100°C, and perform spray granulation to obtain granulated powder;
[0046] Step 4: Pre-press the granulated powder by dry pressing at 20MPa, and final press it by static pressing at 200Mpa to form a blank; place it in a high-temperature furnace, and heat it to 800℃ at a rate of 5℃ / min under a vacuum degree of <0.1MPa, and keep it warm for 1 hour; heat it to 1350℃ at a rate of 8℃ / min, and keep it warm for 2 hours; heat it to 1600℃ at a heating rate of 8℃ and keep it warm for 3 hours; cool it to 1350℃, keep it warm at 80Mpa for 10min, finish sintering, and cool it naturally; grind and polish the surface to obtain high-hardness alumina-based ceramics.
[0047] Embodiment 3: A method for preparing a high-hardness alumina-based ceramic, comprising the following steps:
[0048] Step 1: Preparation of lanthanum boride modified barium titanate: (1) Add 10 parts of barium hydroxide to 15 parts of deionized water, heat to 80°C and stir to dissolve; at room temperature, add 1 part of a dispersion of nano titanium dioxide and 15 parts of ethanol and stir evenly; use ammonia water to adjust the pH to 13.1 to obtain a mixed solution; subject the mixed solution to a hydrothermal reaction at 260°C for 30 hours, cool, wash and dry to obtain barium titanate; (2) Mix 5 parts of lanthanum carbonate, 7.5 parts of sodium metaborate, 4 parts of barium titanate and 0.3 parts of triammonium citrate and ball mill to obtain a mixed powder, which is heat treated at 250°C for 2 hours; after cooling, wash with 5wt% hydrochloric acid and deionized water, dry and grind to obtain lanthanum boride modified barium carbonate;
[0049] Preparation of zirconium oxide modified silicon carbide: (1) placing silicon carbide in a 5wt% acidic solution, stirring at 30°C for 2 hours, adjusting to neutrality, filtering, washing and drying to obtain pretreated silicon carbide; (2) placing 7 parts of pretreated silicon carbide in 3 parts of yttrium stabilized zirconium oxide sol, adding 10 parts of deionized water, 0.05 parts of polyacrylic acid, 0.05 parts of polyethylene glycol and 0.05 parts of polyvinyl alcohol; ball milling, filtering and drying to obtain zirconium oxide modified silicon carbide;
[0050] Step 2: (1) Mix magnesium oxide, nano titanium dioxide, glass powder and niobium pentoxide in a mass ratio of 1:1.2:1.2:0.6 to obtain a sintering aid; (2) Add 3 parts of zirconium oxide modified silicon carbide, 1 part of polyacrylic acid, 2 parts of sodium alginate and 8 parts of the sintering aid into deionized water in sequence, ball mill homogenize, filter and dry to obtain raw material A;
[0051] Step 3: Add raw material A, 88 parts of aluminum oxide, 7 parts of zirconium oxide, 2 parts of lanthanum boride-modified barium titanate, and 1.0 part of triammonium citrate to 20 parts of ethanol in sequence, ball mill homogenize, set the inlet temperature to 300° C., the flow rate to 4.5 kg / h, and the outlet temperature to 100° C., and perform spray granulation to obtain granulated powder;
[0052] Step 4: Pre-press the granulated powder by dry pressing at 20MPa, and final press it by static pressing at 200Mpa to form a blank; place it in a high-temperature furnace, and heat it to 800℃ at a rate of 5℃ / min under a vacuum degree of <0.1MPa, and keep it warm for 1 hour; heat it to 1350℃ at a rate of 8℃ / min, and keep it warm for 2 hours; heat it to 1600℃ at a heating rate of 8℃ and keep it warm for 3 hours; cool it to 1350℃, keep it warm at 80Mpa for 10min, finish sintering, and cool it naturally; grind and polish the surface to obtain high-hardness alumina-based ceramics.
[0053] Based on Example 1, the following comparative examples are set:
[0054] Comparative Example 1: No modification is performed on silicon carbide; the rest is the same as Example 1.
[0055] Comparative Example 2: The amount of zirconium oxide-modified silicon carbide was increased to 4 parts; the rest was the same as Example 1.
[0056] Comparative Example 3: Barium titanate is not modified by lanthanum boride, but is directly used; the rest is the same as Example 1.
[0057] Comparative Example 4: The lanthanum boride-modified barium titanate is replaced with an equal mass of zirconium oxide; the rest is the same as Example 1.
[0058] Performance test: The high-hardness alumina ceramics prepared in the examples and comparative examples were subjected to performance tests: (1) using a Vickers hardness tester with diamond as the indenter material, applying a load of 3 kgf for 10 seconds, and further calculating the Vickers hardness after the test; (2) referring to GB / T6569, using the single-edge notched beam method to test its fracture toughness; (3) referring to GB / T25995, using the Archimedes drainage method to measure its density; the obtained data are shown below:
[0059] sample Vickers hardness (HV) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Density(%) Example 1 1906 7.01 98.3 Example 2 1858 6.82 97.9 Example 3 1831 6.79 97.6 Comparative Example 1 1598 6.23 95.6 Comparative Example 2 1664 6.47 96.4 Comparative Example 3 1709 6.39 95.3 Comparative Example 4 1564 6.20 96.9
[0060] Conclusion: The data in the above table show that a high-hardness alumina-based ceramic with excellent fracture toughness is prepared in this application. The changes in the data of Comparative Examples 1 to 4 effectively illustrate that the lanthanum boride-modified barium titanate and zirconium oxide-modified silicon carbide introduced in the scheme can work together to effectively improve the density and fracture toughness of alumina-based ceramics while ensuring high hardness. The data in Comparative Example 1 show that the direct introduction of silicon carbide without using zirconium oxide to modify it causes the performance to decline, which effectively demonstrates the importance of zirconium oxide-modified silicon carbide; at the same time, it can be found from Comparative Example 2 that excessive introduction will instead cause a decline in mechanical properties. In Comparative Example 3, since the barium titanate was not modified with lanthanum boride, the decline in fracture toughness and Vickers hardness can be clearly seen. At the same time, in Comparative Example 4, an equal mass of zirconium oxide is directly used to replace the lanthanum boride-modified barium titanate, which further reduces the performance, effectively demonstrating the importance of lanthanum boride-modified barium titanate.
[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-hardness alumina-based ceramic, characterized in that: The high-hardness alumina-based ceramic comprises the following raw materials in parts by mass: 88 to 90 parts of alumina, 5 to 7 parts of zirconium oxide, 2 to 4 parts of lanthanum boride-modified barium titanate, 1 to 3 parts of zirconium oxide-modified silicon carbide, 6 to 8 parts of sintering aids, 1 to 2 parts of polyacrylic acid, 1 to 2 parts of sodium alginate, 0.5 to 1.0 parts of triammonium citrate, and 15 to 20 parts of solvent; The preparation method of the lanthanum boride modified barium titanate comprises the following steps: Step 1: add barium hydroxide to deionized water and heat to dissolve; add nano-titanium dioxide and ethanol dispersion at room temperature and stir evenly; use ammonia water to adjust the pH to 12.6-13.2 to obtain a mixed solution; perform a hydrothermal reaction on the mixed solution at 250-270° C. for 20-50 hours, cool, wash and dry to obtain barium titanate; Step 2: Mix the lanthanum compound, sodium metaborate, barium titanate and triammonium citrate and ball-mill to obtain a mixed powder, which is heat-treated at 200-300° C. for 2 hours; after cooling, it is washed with hydrochloric acid and deionized water in sequence, dried, and ground to obtain lanthanum boride-modified barium titanate; The preparation method of zirconium oxide modified silicon carbide comprises the following steps: Step 1: placing silicon carbide in an acidic solution, stirring at 25-35° C. for 1-2 hours, adjusting to neutrality, filtering, washing, and drying to obtain pretreated silicon carbide; Step 2: placing the pretreated silicon carbide in yttrium-stabilized zirconium oxide sol, adding deionized water, polyacrylic acid, polyethylene glycol, and polyvinyl alcohol; ball milling and mixing, filtering and drying, and obtaining zirconium oxide-modified silicon carbide.
2. A high hardness alumina-based ceramic according to claim 1, characterized in that: The lanthanum boride-modified barium titanate comprises the following raw materials in parts by weight: 2 to 5 parts of lanthanum compound, 4 to 8 parts of sodium metaborate, 2 to 4 parts of barium titanate, and 0.2 to 0.5 parts of triammonium citrate.
3. The high hardness alumina-based ceramic according to claim 1, characterized in that: The lanthanum compound includes one or more of lanthanum nitrate, lanthanum oxalate, lanthanum carbonate and lanthanum hydroxide.
4. The high hardness alumina-based ceramic according to claim 1, characterized in that: The sintering aid comprises a composition of magnesium oxide, nano titanium dioxide, glass powder and niobium pentoxide in a mass ratio of 1:(1-1.2):(1.2-1.5):(0.3-0.6).
5. The high hardness alumina-based ceramic according to claim 3, characterized in that: The raw materials in the barium titanate include barium hydroxide and nano titanium dioxide in a mass ratio of (9.5-10):
1.
6. The high hardness alumina-based ceramic according to claim 1, characterized in that: The acidic solution is a 5-6wt% hydrochloric acid solution; the zirconium oxide modified silicon carbide includes the following raw materials in parts by weight: 6-8 parts of pretreated silicon carbide, 2-3 parts of yttrium stabilized zirconium oxide sol, 0.05-0.1 parts of polyacrylic acid, 0.05-0.1 parts of polyethylene glycol, 0.05-0.1 parts of polyvinyl alcohol, and 10-12 parts of deionized water.
7. A method for preparing high-hardness alumina-based ceramics, characterized in that: The preparation of the high-hardness alumina-based ceramic according to any one of claims 1 to 6 comprises the following steps: Step 1: Add zirconium oxide modified silicon carbide, polyacrylic acid, sodium alginate and a sintering aid into deionized water in sequence, homogenize by ball milling, filter and dry to obtain raw material A; Step 2: Add raw material A, aluminum oxide, zirconium oxide, lanthanum boride-modified barium titanate, and triammonium citrate into a solvent in sequence, perform ball milling homogenization, and perform spray granulation to obtain granulated powder; Step 3: Press the granulated powder into a blank, sinter it, grind and polish the surface to obtain a high-hardness alumina-based ceramic.
8. The method for preparing a high-hardness alumina-based ceramic according to claim 7, characterized in that: In step 2, the parameters of spray granulation are: the temperature of the feed port is 250-300° C., the flow rate is 2-5 kg / h, and the temperature of the discharge port is 90-100° C.; in step 3, the parameters of the pressed blank are: dry pressing pre-pressing at 15-20 MPa, and static pressing final pressing at 200-230 MPa; the parameters of the sintering process are: under a vacuum degree of less than 0.1 MPa, heating to 700-800° C. at a rate of 4-5° C. / min, and keeping warm for 1-2 hours; heating to 1300-1400° C. at a rate of 5-10° C. / min, and keeping warm for 2-3 hours; heating to 1500-1700° C. at a heating rate of 5-10° C. and keeping warm for 2-3 hours; cooling to 1300-1400° C., keeping warm for 10-15 min at 80 MPa, sintering is completed, and the temperature is naturally cooled.
Citation Information
Patent Citations
silicon carbide ceramic with excellent wear resistance and high hardness
CN104829253A
Silicon carbide ceramic membrane and preparation method thereof
CN105130441A
Preparation method of polypyrrole modified TiO2 coated LaB6 photodegradation catalyst
CN112264092A
Preparation method of nano lanthanum hexaboride powder
CN115159538A
Semi-conductive ceramic composition and its use in the manufacture of spark plugs
US4999137A
